Reducing Unnecessary Blood Chemistry Testing in the Emergency Department: Implementation of Choosing Wisely. (January 2018) - Venkatesh, Arjun K.; Hajdasz, David; Rothenberg, Craig; Dashevsky, Meir; Parwani, Vivek; Sevilla, Mark; Shapiro, Marc; Schwartz, Ian
Point of care (POC) laboratory testing is used to improve emergency department (ED) throughput but often overuses resources by duplicating formal laboratory testing. This study sought to evaluate the effect of a multimodal intervention on duplicate chemistry testing. This pre-post analysis included all visits to 2 urban EDs between June 2014 and June 2016. The multimodal intervention including provider education, signage, electronic health record redesign, and audit and feedback focused on reducing duplicate chemistry testing. The primary outcome was the number of duplicate chemistry tests per 100 visits. Autoregressive integrated moving-average models were used to account for secular changes. A total of 299 701 ED visits were included. The daily number of duplicate chemistry and POC chemistry tests significantly decreased following the intervention (3.3 fewer duplicates and 10.2 fewer POC per 100 ED visits, P < .0001). This implementation of a multimodal quality improvement intervention yielded substantial reductions in the overuse of blood chemistry testing in the ED.